Complete Solution For The Time Fractional Diffusion Problem With Mixed Boundary Conditions by Operational Method - Aghili, A. (Applied mathematics and nonlinear sciences, 2021)
In this study, we present some new results for the time fractional mixed boundary value problems. We consider a generalization of the Heat - conduction problem in two dimensions that arises during the manufacturing of p - n junctions. Constructive examples are also provided throughout the paper. The main purpose of this article is to present mathematical results that are useful to researchers in a variety of fields.